Characterization of Vegetative Incompatibility in Morchella importuna and Location of the Related-Genes by Bulk Segregant Analysis - Chai, Hongmei; Liu, Ping; Ma, Yuanhao; Chen, Weimin; Tao, Nan; Zhao, Yongchang (Frontiers in Microbiology, 2022)
Vegetative incompatibility (VI) is a widespread phenomenon developed in Morchella importuna, a species of ascomycete fungus that is cultivated on a rapidly expanding scale in China. Understanding the genetic bases of this nonself-recognition phenomenon is beneficial for resolving some problems that are associated with the production of this highly prized edible fungus, such as crossbreeding, strain classification, and pathogen transmission. Vegetative incompatibility is genetically controlled by het genes, organized in two different systems, namely allelic and nonallelic. These het genes have been well characterized in Podospora anserina and Neurospora crassa. In this work, putative het-homologs were identified in the genome of M. importuna, but their low allelic polymorphism in different vegetative compatibility groups (VCGs) suggested that VI in this fungus might not be regulated by these het genes. The progeny derived from vegetative compatible parents became a VCG, while the single-ascospore strains from vegetative incompatible parents were divided into 4 VCGs, and the interaction between the inter-group strains led to the formation of two types of barrages, viz., thin dark line and raised aggregate of hyphae. The Bulk Segregant Analysis confirmed that the genes mimpvic32 and mimpvic33 were linked to VI reactions in M. importuna; nevertheless, the formation of barrages also occurred between the pairs carrying the same allele of these two genes. In sum, the VI control system in M. importuna was complicated, and there were more other allelic or non-allelic VI-related genes.